The morphology, genetic structure, and haplotype distribution of the invasive freshwater snails Biomphalaria straminea and Physa acuta in Guangdong, China - Ping He; Yunyi Hu; Jehangir Khan; Yan Huang; Zhanhong Yuan; Benjamin Sanogo; Du Gao; Jun Liu; De Wu; Jingdiao Chen; Zhongdao Wu; Song Liang; et al. (Tropical Medicine and Health)
Abstract Background Biomphalaria and Physa (order Gastropoda) serve as vectors and reservoirs for infectious agents that affect both humans and animals. This study provides updated insights into the epidemiology, morphology, phylogeny, and haplotype diversity of Biomphalaria and Physa snails in Guangdong Province, southern China. Methods Field surveys were conducted across Guangdong Province from 2016 to 2023. Morphological observations included assessment of snail shape, shell height, and aperture width. Molecular analysis targeted several genes, including Cytochrome c oxidase subunit 1 (COI), internal transcribed spacer (ITS), 18S rRNA, 16S rRNA, and 28S rRNA. Evolutionary trees were constructed with neighbor-joining and maximum likelihood methods. Haplotype networks were generated from COI sequences collected from multiple geographic locations. Results Physa acuta was detected in 92% of surveyed sites, showing broad distribution and notable mitochondrial diversity (15 haplotypes). The dominant haplotype (Hap_3) was shared with sequences from Chile and the Netherlands. In contrast, Biomphalaria straminea was found at 62% of sites and displayed limited genetic variation (2 haplotypes), despite visible morphological dimorphism (red/black forms). Phylogenetic analysis exhibited minimal differences in 16S rRNA and COI gene sequences among turret snail strains, with B. straminea clustering closely to South American lineages. Morphometric analyses revealed significant size differences among strains, for example, Shuanglong B. straminea had a shell width of 8.74 ± 0.26 mm, whereas Zengcheng P. acuta exhibited 11.07 ± 0.90 mm. In contrast, analysis of 28S and 18S rRNA confirmed species boundaries but lacked at the intraspecific level. Conclusions Our analysis of multiple target genes confirms that mitochondrial markers (COI and 16S rRNA) are effective for studying the evolutionary dynamics of freshwater invasive snails. Physa acuta exhibits a widespread distribution and notable genetic diversity across Guangdong, while B. straminea shows limited genetic variation, suggesting strong genetic conservation within the species.